Impedance-based interpretations in 2-dimensional electron gas conduction formed in the LaAlO3/SrxCa1−xTiO3/SrTiO3 system. (June 2016) - Park, Chan-Rok; Moon, Seon Young; Park, Da-Hee; Kim, Shin-Ik; Kim, Seong-Keun; Kang, Chong-Yun; Baek, Seung-Hyub; Choi, Jung-Hae; Kim, Jin-Sang; Choi, Eunsoo; Hwang, Jin-Ha
Abstract: Frequency-dependent impedance spectroscopy was applied to the 2-dimensioanl conduction transport in the LaAlO3 /Sr x Ca1− x TiO3 /SrTiO3 system. The 2-dimensional conduction modifies the electrical/dielectric responses of the LaAlO3 /Sr x Ca1− x TiO3 /SrTiO3 depending on the magnitude of the interfacial 2-dimensional resistance. The high conduction of the 2-dimensional electron gas (2DEG) layer can be described using a metallic resistor in series with two parallel RC circuits. However, the high resistance of the 2-dimensional layer drives the composite system from a finite low resistor in parallel with the surrounding dielectrics composed of LaAlO3 and SrTiO3 materials to a dielectric capacitor. This change in the resistance of the 2-dimensional layers modifies the overall impedance enabled by the presence of the interfacial layer due to Sr x Ca1− x TiO3, which alters the charge transport of the 2-dimensional layer from metallic to semiconducting conduction. A noticeable change is observed in the capacitance Bode plots, indicating highly amplified dielectric constants compared with the pristine SrTiO3 substrates and Sr x Ca1− x TiO3 with a greater Ca content. Highlights: Impedance spectroscopy was applied onto the LaAlO3 / Sr x Ca1− x TiO3 /SrTiO3 system . The 2-dimensional conduction was modeled using an equivalent circuit model. The interfacial Sr x Ca1− x TiO3 layer modifies the 2-dimensional conduction mode. The charge transport is altered from metallic to semiconducting conduction.